Prevalence of Steroid Receptors and HER 2/neu in Breast Cancer Biopsies of Women Living in Puerto Rico - Colón, Edgardo; Reyes, José S.; González-Keelan, Carmen; Climent-Peris, Consuelo (Puerto Rico Health Sciences Journal, 2012)
see manuscript